A tragédia de Iconha/ES em 2020 : modelagem hidrológica e hidrodinâmica bidimensional de evento extremo - Guzzo, Renan Ribeiro (2024)
Natural disasters have become increasingly frequent. On January 17, 2020, the city of Iconha, located in the south of Espírito Santo, suffered the biggest flood of all time, causing significant damage, and leaving 1,919 people left their home, 58 homeless and 4 dead COMPEC (2022). The objective of this work was to evaluate the intensities of sub-daily rainfall occurring in the region of Iconha/ES, compare with the precipitation, duration and frequency curves of the rain gauge station with daily data and generate the hydrograph of the flood of the Iconha river, through the transformation model rain on grid with two-dimensional hydrodynamic flow, considering the rain incident in the river basin varying in time and space through the inverse square distance interpolation method. The information and records confirmed the good security of the model and together with the result of the simulated hydrograph, the existence of distortions in the maximum flow monitoring data from the Iconha River Fluviometric Station was confirmed. Therefore, it is recommended not to use these data for studies of maximum flows, especially with high periods of returns, and it is suggested to use a flood spot and a simulated flow model for adoption in future studies and projects